Law: The Wind Beneath My Wings - Sarah Weddington (Washington University Journal of Law & Policy, 2001)
I believe that a substantial number of law students thirst to make a societal impact through public interest work. Thus, the problem is not a difficulty in mustering enough interest, but rather, the obstacles law students and graduates must face along the way. Accordingly, this Essay traces the disconnect between students’ initial public interest commitment and their later inconsistent professional pursuits, with some thoughts on how to remedy this disparity.
Keywords: Legal assistance to the poor; Law students; Public interest